The Efficacious Integration of the Balanced Scorecard as a Strategic Management Tool: Evidence from UK SMEs - Maddy, George (2020)
The Balanced Scorecard is a strategic management tool that provides a holistic view of an enterprise’s performance on a multidimensional basis and forms linkages between employees’ short-term actions to long-term strategic goals. The extant literature places immoderate emphasis on large enterprises’ experiences with the tool, resulting in a lack of research on the Balanced Scorecard in an SME context, hence the focus of this research on the applicability and utilisation of the tool by SMEs. The research approach adopted in this dissertation includes: (1) an initial survey, which was distributed to 15,891 UK SMEs; followed by (2) a semi-structured interview with two UK SMEs. The main conclusions drawn from this study are (1) most SMEs have not heard of the BSC concept; (2) SMEs place excessive emphasis on financial performance; (3) many firms appear to be employing a system with similar features to the BSC; (4) SMEs’ SPMSs are effective in measuring performance and in managing strategy; (5) SMEs deem their SPMSs to be applicable to their context; (6) there are many likely challenges presented to SMEs considering adopting a SPMS; and (7) there are several CSFs required of SMEs for the successful deployment of a SPMS. This dissertation recommends that: (1) a SPMS should be tailored to an SME’s environment; (2) it is important for SMEs to focus on non-financial performance in addition to financial performance; (3) SMEs should give a thorough consideration of the likely challenges expected when implementing a SPMS; and (4) SMEs should plan ahead for what is required of them for the successful deployment of a SPMS. Keywords: Balanced Scorecard, Strategic Management, Performance Measurement, SME